2016
DOI: 10.1111/clr.12914
|View full text |Cite
|
Sign up to set email alerts
|

Decontamination of titanium implants using physical methods

Abstract: Ti brushes were more effective than curettes (metal or plastic) and Er: YAG laser in decontaminating Ti implant surfaces, although none of these techniques was able to completely eliminate surface contamination. Er: YAG laser was more effective than curettes and Ti brushes in killing the biofilm bacteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 51 publications
7
52
0
Order By: Relevance
“…With erbium lasers, more effective removal of calcified deposits and re‐acquisition of Ti surface were achieved, compared to CP and TC, while preserving the microstructures without any thermal damage; although time required was considerably long because of the lower ablation rate of calcium carbonate compared to that of calculus (calcium phosphate). Scratches on the smooth surface, and uncertainty of debridement, when using a curette, were results like previous reports …”
Section: Discussionsupporting
confidence: 89%
“…With erbium lasers, more effective removal of calcified deposits and re‐acquisition of Ti surface were achieved, compared to CP and TC, while preserving the microstructures without any thermal damage; although time required was considerably long because of the lower ablation rate of calcium carbonate compared to that of calculus (calcium phosphate). Scratches on the smooth surface, and uncertainty of debridement, when using a curette, were results like previous reports …”
Section: Discussionsupporting
confidence: 89%
“…Such procedures inevitably contaminate the surrounding tissues with large amounts of titanium particles and abrasion debris of polishing instruments. In vitro studies have demonstrated titanium brushes, laser and air powder abrasion might be alternatives to curettes, rotating burs, and ultrasonic devices (Al-Hashedi, Laurenti, Benhamou, & Tamimi, 2017;John, Becker, & Schwarz, 2014;Sahrmann et al, 2015). Histologic examinations of peri-implant tissues revealed the presence of a localized mixed chronic inflammatory cell infiltrate dominated by plasma cells and lymphocytes after such therapy.…”
Section: Mechanical Wearmentioning
confidence: 99%
“…Although various methods have been advocated, including air powder abrasion, saline wash, citric acid treatment, laser therapy, peroxide treatment, ultrasonic and manual debridement, and application of topical medication, a gold‐standard is yet to be identified to ensure re‐osseointegration . Al‐Hashedi et al compared the effect of four mechanical decontamination methods (metal and plastic curettes, titanium brushes, and yttrium aluminum and garnet [Er:YAG] laser) on the chemical properties of titanium surfaces. Although titanium brushes achieved greater elimination of bacteria and organic contaminants compared with curettes and Er:YAG laser, none of the methods were able to restore the original surface chemical properties .…”
Section: Introductionmentioning
confidence: 99%